Modulating testosterone pathway: a new strategy to tackle male skin aging? - Bernard P (Dove Medical Press, 2012)
Philippe Bernard1, Thomas Scior2, Quoc Tuan Do11Greenpharma SAS, Orléans, France; 2Pharmacy Department, Benemerita Universidad Autonoma de Puebla, Puebla, MexicoAbstract: In men, the level of testosterone decreases with age. At the skin level, the result is observed as a decrease in density and in a lower elasticity. Identifying compounds that are able to increase the level of testosterone appears to be an attractive strategy to develop new antiaging bioactive ingredients for men. Reverse pharmacognosy was successfully applied to identify new natural compounds able to modulate testosterone levels. Among several in silico hits, honokiol was retained as a candidate as it has the greatest potential to become an active ingredient. This result was then validated in vitro on aromatase and 5-alpha-reductase type 1 and 2, which are two types of enzymes implicated in the degradation of free testosterone. Indeed, honokiol was identified as an inhibitor of aromatase, with a half-maximal inhibitory concentration (IC50) of about 50 µM. In addition, honokiol was shown to be an inhibitor of 5-alpha-reductase type 1, with an IC50 of about 75 µM. Taken together, these data indicate that honokiol modulates testosterone levels, and its structure has the potential to serve as a lead for future designs of highly selective inhibitors of 5-alpha-reductase type 1.Keywords: reverse pharmacognosy, honokiol, testosterone, man cosmetics, dermopharmacy